Islamic Love Stories: How Indonesian Soap Opperas Presented Islamic Version of Romantic Love in the 2000s - Wina Sumiati (Tsaqofah, 2023)
During Ramadhan month in the 2000s, most Indonesian TV stations used to air Islamic-themed soap operas. However, the stories of those soap operas did not represent Islamic values. Rather than showing Islamic messages in their stories, most scenes of those soap operas were all about melodrama and mysticism. This research aims to analyze and compare two Islamic-labeled soap operas, Lorong Waktu 3 (2002) and Kiamat Sudah Dekat (2005), claimed as the real Islamic stories by Dedi Mizwar. While I intend to prove Mizwar's claim, I also will focus on examining the romantic scenes in both soap operas. I use qualitative methods to analyze the research objective by collecting primary sources digitally on YouTube and secondary sources in online-offline libraries. The videos of Mizwars' soap operas are available and open-accessed on YouTube, so obtaining the relevant primary sources is effortless. After researching, I found that melodrama and mysticism popularities of many Islamic labeled soap operas did not influence the romantic love stories of Mizwar's production. Both Lorong Waktu 3 and Kiamat Sudah Dekat beautifully convey how Islam confines a romantic relationship to Indonesian Muslim society. All in all, this research shows the filmmaker succeeded in criticizing and changing the image of most soap opera characters that previously did not represent Islamic lessons.